THE FEATURES OF FOREIGNIZATION STRATEGIES IN THE ENGLISH TRANSLATION OF NOVEL “BYGONE DAYS” (The Conference Hub, 2025)
This article analyzes the application of the foreignization strategy in the English translation of Abdulla Qodiriy’s novel O‘tkan Kunlar (Bygone Days). The study explores how the cultural, social, and historical features of Uzbek society reflected in the original text are rendered in translation. The article also discusses the linguistic and cultural techniques used by the translator to preserve the national identity of the source text.